Comparison between Sequestrectomy with or without Nucleotomy in Surgical Treatment of Herniated Lumbar Disc - محفوض مفيد; عبد الرحمن محمد; سليمان علاء (Latakia University Journal -Medical Sciences Series, 2021)
Aim: To compare sequestrectomy without nucleotomy vs. sequestrectomy with nucleotomy in the surgical treatment of lumbar disk herniation, regarding the continuation of a postoperative low back pain and getting good surgical results in improving radicular pain, muscle weakness and recurrence rate between the two surgical techniques. methods: 48 patients were included and 4 patients were excluded. The follow up period were divided into two periods. The mean of the first period was 4.7±0.9 months and the mean of the second period was 13.5±3.06 months and the longest follow up period was 21 months. The patients were divided into two groups: Group A where patients underwent Sequestrectomy without Nucleotomy and Group B where patients underwent Sequestrectomy with Nucleotomy. Results: We were able to follow up 21 patients in Group A “13 males and 8 females, the median age 45 years” and 23 patients in Group B “18 males and 5 females, the median age 43 years”. The median VAS for LBP in group A decreased by 75.75% where it was decreased by 53.22% in group B (p-value=0.0001). The median VAS for radicular pain decreased by 94.2% in group A and by 89.15% in group B (p-value=0.08). The postoperative functional status represented by (ODI%) was at the end of the follow up period 21.7% in group A and 39.4% in group B (p-value=0.002). Muscle weakness was seen only as foot drop (complete or partial) and there were complete improvement in foot drop. in 4 patients out of 7 patients in group A whereas there were complete improvement in 4 patients out of 6 patients in group B (p-value=0.9). Recurrence was seen in one patient (4.7%) in the second follow up period in group A and in two patients (8.6%) in group B (one in each follow up period). (p-value=0.7) Conclusions: We concluded that Sequestrectomy without Nucleotomy doesn’t increase recurrence rate compared to Sequestrectomy with Nucleotomy in case the annulus fibrosis tear was less than or equal to 5 mm. Regarding clinical results, we found the results close in radicular pain and muscle weakness improvement whereas low back pain continuation and postoperative functional status were clearly better in the group of Sequestrectomy without Nucleotomy.